Assessing soil quality status in Ghana's oil palm smallholder plantations - Kannesan, Joseph; Rajoo, S. Keeren; Abdu, Arifin; Karam, S. Daljit; Rosli, Zamri; Izani, Norul; Zulperi, Dzarifah (Malaysian Society of Soil Science, 2023)
Despite continuous governmental initiatives, oil palm yields in Ghana is significantly lower than Southeast Asian nations, being unable to even satisfy domestic demand. It hypothesized that one of the main limiting factors to oil palm production in Ghana is due to poor soil suitability. However, there is limited soil studies in Ghana oil palm plantations. Thus, this study was conducted to evaluate the soil fertility status of smallholder oil palm plantations in the Brong Ahafo and Ashanti Regions of Ghana. By understanding the soil condition, appropriate land management strategies can be conducted to increase the productivity of Ghanas smallholder oil palm plantations. Soil sampling was conducted in four plantations, two each in the Ashanti Region and Brong Ahafo Region, with 25 samples collected from each plantation. Samples were taken from between palm trunks, at a depth of 0-20 cm, using a soil auger. Appropriate soil analyses were conducted to determine the chemical soil properties of the samples. Additionally, the Nutrient Index was calculated to evaluate the soils sufficiency for crop nutrition. The soil analysis revealed differences between the regions, with Brong Ahafo exhibiting lower soil quality, particularly in organic matter and available phosphorus. Both regions displayed low Nutrient Index values, indicating inadequate soil nutrient supply for optimal crop growth. To enhance smallholder productivity and profitability, addressing knowledge gaps and providing support in land preparation, field maintenance, and fertilizer access is crucial. Government intervention and subsidies for smallholders can boost yields, meet domestic palm oil demand, and improve farmers' livelihoods in Ghana.